Chemical weathering and CO2 consumption in the source of the alpine catchment. Issue 6 (9th June 2022) - Wang, Lei; Yang, Jian; Wang, Zhaohan; Zhao, Zeyang; Han, Yuping
Abstract: The chemical composition of the river indicates chemical weathering, which is the main source of ions and the most important avenue for carbon sink in the river. The hydrochemical characteristics of alpine catchment can provide the basis for clarifying the chemical weathering process and CO2 consumption, which is meaningful for the chemical weathering evolution law of the alpine catchment and even the Third Pole. The Yarlung Tsangpo River is the most typical river in the alpine catchment and the biggest river of the Third Pole. In this study, the river water samples were collected in March and September 2019 from the main stream at the upper reaches of Yarlung Tsangpo River above Lhatse County, as well as main tributaries Dogxung Tsangpo and Damqog Tsangpo. Based on the comparative analysis of the water samples in different seasons, the following conclusions are reached: precipitation contributes little to the ion content of rivers, and ions mainly come from chemical weathering, the main type of water body is HCO3 − -SO4 2− -Ca 2+ ; carbonate rock weathering in the main stream of Yarlung Tsangpo River contributes more to the ions of river than that in other tributaries; the CO2 consumption is mainly caused by silicate rock weathering and carbonate rock weathering, and the carbon weathering rate increases faster than that of silicate weathering rate from March to September 2019; the consumption rate of CO2 in the wet season is higher than that in the dry season. HIGHLIGHTS: The seasonal differences of chemical differentiation between dry season and wet season in the alpine catchment are analyzed. Study on the water chemical characteristics and ion source analysis of the upper reaches of Yarlung Tsangpo River. The absorption rate of CO2 by weathering of silicate rock and carbonate rock are studied according to weathering rate. Graphical Abstract